A Note on Physical and Mechanical Properties of Diospyros microphylla - Sekhar, A. C.; Rawat, N. S. (Indian Forester, 1966)
Physical and mechanical tests were done in Green, Air-Dry and Kiln-Dry condition on standard clear specimens of Diospyros microphylla, received from the Kanara Eastern Division, Bombay. The results have been compared with teak and Diospyros melanoxylon received from Nagpur, Bombay and already tested and reported previously.